Manajemen Kepala Sekolah Dalam Melaksanakan Budaya Sumang Opat di Lingkungan Madrasah Aliyah Negeri 1 Aceh Tengah - Musradinur, Musradinur (Intelektualita: Journal of Education Sciences and Teacher Training, 2025)
The leadership of the madrasah principal is very central in creating changes that can influence group activities towards setting and achieving goals, can be seen as a person who uses applicable structures and procedures to achieve the goals of the madrasah organization. As time goes by, culture or customs are rarely used as a reference or foundation in implementing life values. In the educational environment itself, due to technological developments, advances in the era and even due to the pandemic that is currently hitting the world, it can have an impact on the loss of cultural order or customs that apply in the community that are applied in the school environment, moral decadence is inevitable, education is only focused on transferring knowledge and seems no longer on instilling educational values ​​in the form of character, morals and national personality that loves culture. The management of the Madrasah Principal in implementing the Sumang Opat culture in the environment of Madrasah Aliyah Negeri 1 Aceh Tengah begins with planning, organizing, implementing, supervising and evaluating management is the entire process of thinking, grouping all tasks, responsibilities, authorities, in determining all activities carried out in order to achieve the goals of the madrasah. The management of the madrasah principal in developing the Sumang Opat culture, where the madrasah principal seeks to improve the implementation of the Sumang culture, organizes tasks to each personnel according to educational qualifications, in this case the madrasah principal takes action with planning and paying attention to discipline and responsibility in acting. The madrasah principal also supervises and evaluates teachers and students in implementing the Sumang Opat culture in the environment of Madrasah Aliyah Negeri 1 Aceh Tengah.